Reviewing the Role of the Coordinating Board for Campus Da’wah Institutions (BKLDK) In Spreading Radicalism - Setia, Paelani; Syarif, Dede (IAIN Ponorogo, 2022)
This paper discusses a driving factor that contributes to the rising of radicalism on major campuses around Bandung. The research focuses on the Coordinating Board for Campus Da'wah Institutions (Badan Koordinasi Lembaga Dakwah Kampus-BKLDK), a sub-organization of Hizbut Tahrir Indonesia (HTI) campaigning Khilafah ideology around campuses in the Bandung area, West Java. The research deploys a qualitative method with data collection through participant observation ories in BKLDK activities, interviews with key informants, and document review. Referring to the circulation of Khilafah ideology carried out by BKLDK, this study argues that the rising of a narrative on radicalism among campuses is due to the absence of differentiation in understanding and handling radicalism itself. Focusing on the role of BKLDK, considered a radical movement, this organization and on spreading ideas without violence, precisely succeeded in mainstreaming Khilafah discourse among students on campuses around Bandung through a strategy of distributing leaflets as reading material and public discussions. Meanwhile, a government and campuses strategy to counterbalance the discourse of radicalism tends to generalize between the radicalism of ideas and radicalism as a violent movement